2013
DOI: 10.1063/1.4838015
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of red spectral shifts at CdTe grain boundaries

Abstract: The best research-cell efficiencies for CdTe thin-film solar cells have recently increased from 17.3% to 20.4%. Despite these impressive recent gains, many improvements in device technology are necessary to reach the detailed-balance efficiency limit for CdTe-based (singlejunction, non-concentrator) solar cells of ~32%. Improvements will increasingly rely on knowledge of the fundamental relationships between processing, electrical properties of defects, and device performance. In this study, scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…15,16 Additionally, some researchers have found that GBs exhibit higher recombination rates (S x B 10 4 cm s À1 ) than those of the grain interiors. 17 Contrastingly, other researchers have found that after Cl treatment (a key step to improve the CdTe efficiency), 18 the GBs no longer act as recombination centers, but actively contribute to carrier collection. 8,9,[19][20][21][22] The increased carrier collection at the GBs is explained by the presence of a local space charge region with a width of about 100-350 nm, which is beneficial to electron-hole pair separation.…”
Section: Introductionmentioning
confidence: 95%
“…15,16 Additionally, some researchers have found that GBs exhibit higher recombination rates (S x B 10 4 cm s À1 ) than those of the grain interiors. 17 Contrastingly, other researchers have found that after Cl treatment (a key step to improve the CdTe efficiency), 18 the GBs no longer act as recombination centers, but actively contribute to carrier collection. 8,9,[19][20][21][22] The increased carrier collection at the GBs is explained by the presence of a local space charge region with a width of about 100-350 nm, which is beneficial to electron-hole pair separation.…”
Section: Introductionmentioning
confidence: 95%
“…They can exist in various forms and play important roles in determining material properties, and thus have been one of the most active research topics in materials science [1][2][3][4][5][6]. For example, segregation of impurities to the GBs is an effective way to purify materials, thus improving material quality for device applications [7][8][9][10][11][12]. GBs also increase phonon scattering, allowing the thermoelectric properties of a material to be improved by intentionally controlling its GB size [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 (a) shows a detailed region of a CL map and a CL profile around a GB Figure 3 (b). It can be fit with a simple one-dimensional diffusion model [43][44][45][46] describing the decay of the luminescence intensity from the grain interior (x GI > 0) towards the grain boundary (x = 0).…”
Section: Asmentioning
confidence: 99%